2015
DOI: 10.1149/2.0231601jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mass Transport in Redox Flow Batteries by Tailoring Flow Field and Electrode Design

Abstract: In this study, we investigate the mass transport effects of various flow field designs paired with raw and laser perforated carbon paper electrodes in redox flow batteries (RFBs). Previously, we observed significant increases in peak power density and limiting current density when perforated electrodes were used in conjunction with the serpentine flow field. In this work, we expand on our earlier findings by investigating various flow field designs (e.g., serpentine, parallel, interdigitated, and spiral), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 28 publications
(49 reference statements)
3
116
0
Order By: Relevance
“…Additionally, increasing flow rate increases the limiting current density for the cell, again due to improved mass transfer in the porous electrode. This behavior is anticipated from prior experimental reports, 17,18,23,28 as well as our model, which indicates that faster mass transfer rates (smaller θ) lead to improved electrochemical performance. Figure 6b illustrates another trend previously reported in literature, 45 where increasing the active material concentration for one field (SFF) at a fixed flow rate (2 mL min −1 ) alleviates cell polarization despite a decrease in electrolyte conductivity ( Figure 5).…”
Section: Experimental Results and Model Fittingsupporting
confidence: 86%
See 3 more Smart Citations
“…Additionally, increasing flow rate increases the limiting current density for the cell, again due to improved mass transfer in the porous electrode. This behavior is anticipated from prior experimental reports, 17,18,23,28 as well as our model, which indicates that faster mass transfer rates (smaller θ) lead to improved electrochemical performance. Figure 6b illustrates another trend previously reported in literature, 45 where increasing the active material concentration for one field (SFF) at a fixed flow rate (2 mL min −1 ) alleviates cell polarization despite a decrease in electrolyte conductivity ( Figure 5).…”
Section: Experimental Results and Model Fittingsupporting
confidence: 86%
“…Several recent studies have shown that large performance gains are possible in RFBs through changes in the flow field type, as well as the electrode geometry or morphology. 15,17,18,[20][21][22][23][24] While such reports represent excellent engineering efforts to improve RFB power density, increases in mass transfer rates are rarely quantified, arguably due to insufficient knowledge of relevant transport processes within the ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, electrolyte design for NAqRFBs must consider viscosity as a key materials optimization parameter, and, in the case of this work, MeCN vastly outperforms PC as a base solvent for a low viscosity and high conductivity electrolyte. Figure 4d hint that mass transfer rates are critical in determining the total ASR for RFBs, but only a handful of prior reports have systematically studied mass transfer effects in AqRFBs, 32,34,[60][61][62] with no reports directly relating to NAqRFBs. To begin addressing this knowledge gap, Figure 5 highlights nonaqueous flow cell performance for the PC-and MeCN-based electrolytes, with a Daramic separator, at 4 flow rates spanning greater than an order of magnitude.…”
Section: Nyquist Plots Inmentioning
confidence: 99%